(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
In the editorial, Nando dalla Chiesa introduces the issue 3/2023, in which reflections and analysis are articulated around the birth of the Italian Scientific Society for Mafia and Antimafia Studies (SISMA), the European Directive on the management of confiscated property, and the Antimafia Parliamentary Commission. The issue is completed by the usual analysis of the History and Memory section. At the end of the editorial it is possible to find the complete statutes of the Italian Scientific Society for Studies on Mafias and Antimafias (SISMA)